2010
DOI: 10.1093/annonc/mdq210
|View full text |Cite
|
Sign up to set email alerts
|

p16 expression in oropharyngeal cancer: its impact on staging and prognosis compared with the conventional clinical staging parameters

Abstract: p16 is the most relevant prognostic marker in OPSCC and should be considered for inclusion into the official staging system of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 23 publications
9
85
1
4
Order By: Relevance
“…Overexpression of p16 was observed in the present tumor specimens, confirming the results of a number of previous studies (4,(32)(33)(34)(35)(36), as well as demonstrating the strong association between p16 and HPV-infection in tonsillar carcinomas. The majority of these specimens exhibited p16 expression of medium intensity, while a further 11% showed strong p16 expression.…”
supporting
confidence: 92%
“…Overexpression of p16 was observed in the present tumor specimens, confirming the results of a number of previous studies (4,(32)(33)(34)(35)(36), as well as demonstrating the strong association between p16 and HPV-infection in tonsillar carcinomas. The majority of these specimens exhibited p16 expression of medium intensity, while a further 11% showed strong p16 expression.…”
supporting
confidence: 92%
“…needed. [10][11][12]19,20 Here, we used RPA to explore new stage groupings for HPV-positive OPC and found that incorporation of NPC N categories resulted in better distribution of patients between groups than did use of the traditional OPC N categories.…”
Section: Discussionmentioning
confidence: 99%
“…Others have similarly found that T category but not N category predicts survival for patients with HPV-positive OPC. 10,19,21,22 In an analysis of Surveillance, Epidemiology, and End Results data, Keane et al 13 found that the effect of T category on head and neck cancer-specific mortality increased between 1997 and 2008 (P for interaction = .01), whereas the effect of N category declined during this same period (P for interaction , .001), and overall stage was not predictive of outcome. 13 Similarly, Ward et al 10 retrospectively analyzed 266 patients with OPC and found that the TNM system adequately staged patients with HPV-negative but not HPV-positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2a/INK4a located on 9p21 is frequently inactivated in oral epithelial pre-cancer and cancer via the following events: LOH, hypermethylation, deletion, mutation. The loss of p16INK4A expression defines a subgroup of oropharyngeal cancer patients with worse clinical outcome [16] whereas p16 protein over-expression has been proposed as surrogate marker of HPV infection initially in cervical cancer by Amortegui et al, [25,26], followed by squamous cell carcinomas from other sites than uterine cervix [27], and especially in Head and Neck Cancers [28,29].…”
Section: Discussionmentioning
confidence: 99%